2022
DOI: 10.1111/bjet.13286
|View full text |Cite
|
Sign up to set email alerts
|

Learning analytics application to examine validity and generalizability of game‐based assessment for spatial reasoning

Abstract: Game-based assessment (GBA), a specific application of games for learning, has been recognized as an alternative form of assessment. While there is a substantive body of literature that supports the educational benefits of GBA, limited work investigates the validity and generalizability of such systems. In this paper, we describe applications of learning analytics methods to provide evidence for psychometric qualities of a digital GBA called Shadowspect, particularly to what extent Shadowspect is a robust asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The authors demonstrated that this approach can be used to determine the effectiveness of test items and identify the items that need to be revised to improve the overall reliability of an exam. Kim et al (2022) utilised traced events collected in a game-based learning environment to evaluate the psychometric qualities of game-based assessment of students' spatial reasoning skills. The authors demonstrated that combining game-based assessment and learning analytics methods is a promising new approach to assessing students' cognitive skills.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…The authors demonstrated that this approach can be used to determine the effectiveness of test items and identify the items that need to be revised to improve the overall reliability of an exam. Kim et al (2022) utilised traced events collected in a game-based learning environment to evaluate the psychometric qualities of game-based assessment of students' spatial reasoning skills. The authors demonstrated that combining game-based assessment and learning analytics methods is a promising new approach to assessing students' cognitive skills.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…Nicolaidou et al (2021) showed that the more hours the young adults in their study played digital puzzle games, the higher their spatial reasoning skills. Kim et al (2023) European Union's Digital Education Action Plan -.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Validation Surveys emerged as an important tool utilized by experts. Systematic assessment, using a Likert scale, carefully examines the quality, accuracy, and overall design of learning materials [17] . The culmination of expert perspectives triggers an iterative refinement process, ensuring content alignment with pedagogical goals.…”
Section: Introductionmentioning
confidence: 99%